(untitled) (American Journal of Islam and Society, 2016)
Scholars of Islam in Southeast Asia and the history of the Malay-Indonesian world have long been aware of periods of intense contacts between the Ottoman Empire and the region. Most widely known in this context are the political exchanges between the Sultanate of Aceh and the Ottoman Empire of the sixteenth century in the face of Portuguese maritime domination in Southeast Asia. Regional calls for Ottoman aid against the expanding European powers by Muslim rulers were voiced in the nineteenth century. Despite this lapse in documented political contacts, however, connections between the two regions were also sustained and developed further throughout the intervening centuries on a variety of levels, most prominently in the economic, religious, and intellectual spheres. Despite the pioneering work of scholars such as Anthony Reid since the 1960s, these connections, including inter alia the holy cities and Yemen’s Hadhramaut region, both important centers of Islamic learning for Southeast Asian Muslims and the source of strong migrant communities settling in the Malay-Indonesian world, have received scant scholarly attention. It is against this background that the British Academy-funded research project “Islam, Trade, and Politics across the Indian Ocean” and the volume at hand, which represents one of its major fruits, brings together new innovative research on all of the various aspects of this particular relationship. Hereby it must be noted that its scope extends at times well beyond the Ottoman era also into the Republican era, and that, importantly, much of the documentary evidence relied upon derives from newly discovered archival sources. The volume is divided into three thematic parts, preceded by two introductory chapters by the editors and Anthony Reid, respectively, which set the stage for the remainder of the book by reviewing the relationship’s general ...